SEED VIGOUR OF SPELT PRODUCED AT THE MAIZE RESEARCH INSTITUTE, ZEMUN POLJE - Lazarević, Tijana; Petrović, Tanja; Todorović, Goran; Sečanski, Mile; Golijan-Pantović, Jelena; Lekić, Slavoljub (Journal of Agricultural Sciences (Belgrade), 2022)
Spelt (Triticum spelta L.) has been increasingly attracting producers due to biological properties and chemical composition of its seeds. As high-quality seeds are necessary for successful production, vigour of organically and conventionally produced spelt seeds have been studied and results are presented in this paper. The seeds of the variety Nirvana produced by both methods at the Maize Research Institute, Zemun Polje in 2015 were observed. According to results, total germination of conventionally and organically produced spelt seeds amounted to 99% and 93%, respectively. The percentage of abnormal seedlings of spelt produced by both methods amounted to 1% on average. The participation of diseased and dead seeds was higher in organically produced seeds (6%) than in conventionally produced seeds (0%). After the seed accelerated ageing test, the higher germination was observed in conventionally produced seeds (75%) than in organically produced seeds (68%). The results obtained by the electrical conductivity test indicated that the conventionally produced spelt seeds (32.33 µS/cm g) were classified into the category of low-vigour seeds in comparison to organically produced spelt seeds (27.65 µS/cm g).